1994
DOI: 10.2466/pms.1994.78.1.19
|View full text |Cite
|
Sign up to set email alerts
|

“Experimental Amnesia” Induced by Emotional Items

Abstract: Tulving described an effect of retrograde amnesia in a free-recall task of word lists, produced by inserting items having priority in recall. Other authors confirmed the amnesic effect without giving instructions for priority both in recall and in recognition tasks. The effect was explained by Tulving as a premature termination of encoding processes. The similarity between these experiments and the researches aimed at reproducing amnesia by emotional trauma led us to hypothesize that the two phenomena might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…We favor the latter in view of the enduring nature of the amnesia we observe in the E-2 effect. Note that previously reported retrograde amnesia effects (11,23) were limited in temporal duration, spanning the order of 1 s. Our data show that an emotional manipulation leads to a robust retrograde effect that spans at least 6 s or two stimuli. A group (patient, control) ϫ oddball type (emotional, perceptual) ϫ position (oddball-1, oddball, oddball ϩ 1) 2 ϫ 2 ϫ 3 ANOVA (assumes variance in patient population is equal to that in normals) revealed a significant group ϫ oddball interaction (F 1.0, 1.0 ϭ 196.6 P Ͻ 0.05) and a trend for the group ϫ oddball ϫ position interaction (F 1.0, 1.0 ϭ 60.0 P ϭ 0.08).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…We favor the latter in view of the enduring nature of the amnesia we observe in the E-2 effect. Note that previously reported retrograde amnesia effects (11,23) were limited in temporal duration, spanning the order of 1 s. Our data show that an emotional manipulation leads to a robust retrograde effect that spans at least 6 s or two stimuli. A group (patient, control) ϫ oddball type (emotional, perceptual) ϫ position (oddball-1, oddball, oddball ϩ 1) 2 ϫ 2 ϫ 3 ANOVA (assumes variance in patient population is equal to that in normals) revealed a significant group ϫ oddball interaction (F 1.0, 1.0 ϭ 196.6 P Ͻ 0.05) and a trend for the group ϫ oddball ϫ position interaction (F 1.0, 1.0 ϭ 60.0 P ϭ 0.08).…”
Section: Discussionsupporting
confidence: 57%
“…Thus, memory for E-1 nouns was significantly impaired relative to P-1 nouns. Note that distinctiveness of emotional stimuli is a potential confound in previous investigations of emotion-induced memory disruption (6,10,11,25). Furthermore, the blocking effect of propranolol on the enhancement of memory for E nouns cannot be explained in terms of a blockade of enhanced memory for oddball stimuli (the von Restorff effect; ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrograde and anterograde amnesic potential of emotional events (Tulving, 1969;Loftus and Burns, 1982;Christianson, 1984;Angelini et al, 1994) has attracted less neurobiological attention. Strange et al (2003) showed that enhanced recall of aversive nouns is coupled to enhanced forgetting of preceding neutral nouns, with both effects eliminated by propranolol.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, emotion-induced amnesia can be modeled by oddball paradigms where privileged encoding of an emotional oddball into episodic memory (the emotional von Restorff effect; von Restorff 1933; Wallace 1965) disrupts encoding of preceding and following neutral stimuli (Tulving 1969;Detterman 1975;Angelini et al 1994), particularly if the oddball is aversive (Strange et al 2003;Hurlemann et al 2005). One hypothesis is that aversive emotion interferes with episodic encoding by activating an ensemble of neurochemical responses related to acute stress (de Kloet et al 2005).…”
Section: Introductionmentioning
confidence: 99%